Effectiveness of low‐dose pregabalin in three patients with Lewy body disease and central neuropathic pain. Issue 2 (27th January 2016) - Ukai, Katsuyuki; Fujishiro, Hiroshige; Ozaki, Norio
Abstract: Many patients with Lewy body disease complain of pain, and their pain may be associated with this disease. Recently, pain has become a focus of attention in Parkinson's disease, but there is little information regarding pain in patients who have dementia with Lewy bodies. We used pregabalin to treat three Lewy body disease patients with chronic pain that may have been related to degeneration of central neurons. All three patients responded well to pregabalin at 25–50 mg/day. To our knowledge, there have been no previous reports of pregabalin showing efficacy for central neuropathic pain in Parkinson's disease or Lewy body disease.